The Development of Qur’anic Exegesis During the Period of Stagnation: Methodology, Key Madrasah Figures, and Intellectual Dynamics - Rifani Akhiyar; Komaruddin Sassi (Bulletin of Pedagogical Research, 2025)
Qur’anic exegesis has been practiced since the time of the Prophet Muhammad (peace be upon him) and has continued to develop across different historical periods, including the era of the Prophet and his Companions, the era of the Tābiʿīn, and the modern period. This study aims to examine the historical development of tafsir across these three major periods. The research employs a library-based method, gathering relevant information and data from various sources such as books, scholarly notes, and research articles. The findings reveal that during the Prophet’s lifetime, Qur’anic interpretation continued to evolve, eventually giving rise to diverse exegetical schools and methods. In the period of the Companions, the Qur’an was interpreted primarily through riwāyah (transmitted reports), and at times through ijtihād when no direct explanation from the Prophet was available. The era of the Tābiʿīn marks further development of tafsir, characterized by the emergence of interpretive traditions centered in Makkah, Madinah, and Iraq. This study contributes to Qur’anic studies by providing a structured historical mapping of tafsir evolution, clarifying the foundational epistemological shifts across periods, and offering a comparative framework that can support future research on the continuity and transformation of exegetical methods from classical to modern times.